Effect of storage and aging conditions on the flexural strength and flexural modulus of CAD/CAM materials - Porto, Thiago Soares; Roperto, Renato Cassio; Akkus, Anna; Akkus, Ozan; Teich, Sorin; Faddoul, Fady; Porto-neto, Sizenando Toledo [UNESP]; Campos, Edson Alves [UNESP] (Japanese Soc Dental Materials Devices, 2019)
Computer-aided design/computer-aided manufacturing (CAD/CAM) materials were submitted to thermocycling, to identify changes in mechanical behavior. Four CAD/CAM materials were divided in four subordinate groups (n=9): (1) dry out for 7 days, (2) distilled water at 37 degrees C for 7 days, (3) 60,000 thermocycles, and (4) 120,000 thermocycles. Following thermocycling, samples were submitted to three-point bending test. Two-way ANOVA and post-hoc Tukey's test were performed (alpha=0.05). The IPS e.max CAD had a flexural strength of 396 +/- 75 MPa and flexural modulus of 84 +/- 11 GPa, followed by Vita Enamic with values of 153 +/- 17 MPa and 28 +/- 5 GPa respectively. The flexural strength recorded for Lava Ultimate was 149 +/- 28 MPa and the flexural modulus was 12 +/- 3 GPa. Vitablocs Mark II had the lowest flexural strength values (125 +/- 10 MPa) and a flexural modulus of 49 +/- 15 GPa. Although polymer-based materials have similar mechanical properties compared to ceramics, they are affected by thermo cycling conditions.
Keywords: Ceramics; CAD/CAM; Chipping; Brittle ceramics; Flexural strength